Circadian Rhythms and Melatonin Metabolism in Patients With Disorders of Gut-Brain Interactions - Fowler, Sophie; Hoedt, Emily C.; Talley, Nicholas J.; Keely, Simon; Burns, Grace L. (Frontiers in Neuroscience, 2022)
Circadian rhythms are cyclic patterns of physiological, behavioural and molecular events that occur over a 24-hour period. They are controlled by the suprachiasmatic nucleus (SCN), the brains master pacemaker which governs peripheral clocks and melatonin release. While circadian systems are endogenous, there are external factors that synchronise the SCN to the ambient environment including light/dark cycles, fasting/fed state, temperature and physical activity. Circadian rhythms also provide internal temporal organisation which ensures that any internal changes that take place are centrally coordinated. Melatonin synchronises peripheral clocks to the external time and circadian rhythms are regulated by gene expression to control physiological function. Synchronisation of the circadian system with the external environment is vital for the health and survival of an organism and as circadian rhythms play a pivotal role in regulating GI physiology, disruption may lead to gastrointestinal (GI) dysfunction. Disorders of gut-brain interactions (DGBIs), also known as functional gastrointestinal disorders (FGIDs), are a group of diseases where patients experience reoccurring gastrointestinal symptoms which cannot be explained by obvious structural abnormalities and include functional dyspepsia (FD) and irritable bowel syndrome (IBS). Food timing impacts on the production of melatonin and given the correlation between food intake and symptom onset reported by patients with DGBIs, chronodisruption may be a feature of these conditions. Recent advances in immunology implicate circadian rhythms in the regulation of immune responses, and DGBI patients report fatigue and disordered sleep, suggesting circadian disruption. Further, melatonin treatment has been demonstrated to improve symptom burden in IBS patients, however the mechanisms underlying this efficacy are unclear. Given the influence of circadian rhythms on gastrointestinal physiology and the immune system, modulation of these rhythms may be a potential therapeutic option for reducing symptom burden in these patients.